2011
DOI: 10.5339/qfarf.2011.bmp2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Attitudes Toward Pharmaceutical Care in Qatar

Abstract: Objectives:The study objectives were to investigate Qatar pharmacy students' attitudes toward pharmaceutical care (PC), to identify the factors that influence their attitudes, and to recognize their perceived barriers for PC provision. Methods: A cross-sectional and online survey of Qatar pharmacy students was conducted. Results: Over 4 weeks, 46 surveys were submitted (88% response rate). All respondents agreed that the pharmacist's primary responsibility is to prevent and resolve medication therapy problems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 18 publications
(24 reference statements)
1
31
0
1
Order By: Relevance
“…In Al-Arifi`s 16 study, 95.2% felt that pharmaceutical care movement will improve the patients` health, 94.9% thought that the practice of pharmaceutical care is valuable, 85% that all pharmacists should perform pharmaceutical care, whereas, about two third (64.5%) thought that students should perform pharmaceutical care during their clerkship, were reported by pharmacy students (n=214). According to El Hajj 27 our results suggest that the inclusion of a separate course on pharmaceutical care in the curriculum did not appear to be essential to nurture the students' positive attitudes. Our study data suggest that participants, who had more practical experience hade more positive attitudes toward pharmaceutical care.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In Al-Arifi`s 16 study, 95.2% felt that pharmaceutical care movement will improve the patients` health, 94.9% thought that the practice of pharmaceutical care is valuable, 85% that all pharmacists should perform pharmaceutical care, whereas, about two third (64.5%) thought that students should perform pharmaceutical care during their clerkship, were reported by pharmacy students (n=214). According to El Hajj 27 our results suggest that the inclusion of a separate course on pharmaceutical care in the curriculum did not appear to be essential to nurture the students' positive attitudes. Our study data suggest that participants, who had more practical experience hade more positive attitudes toward pharmaceutical care.…”
Section: Discussionmentioning
confidence: 59%
“…In Qatar, research results have also revealed pharmacy students' positive attitudes toward pharmaceutical care. 27 All respondents agreed that the pharmacist's primary responsibility is to prevent and resolve medication therapy problems. Most respondents believed that pharmaceutical care provision is professionally rewarding and that all pharmacists should provide pharmaceutical care (93% and 91% of respondents, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Qatar investigating pharmacy students' perceptions to pharmaceutical care, where they work closely with healthcare professionals and patients, demonstrated that senior students who have completed more internships may have noted the mismatch between the theory and the practice. (El Hajj, Hammad, & Afifi, 2014). The same could be for IPE hence educators should inform students that on entering the practice they may need to be 'agents of change' to promote and advance collaborative working (Rotz, Dueñas, Grover, Headly, & Parvanta, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives include, but are not limited to, offering continuing professional development sessions on interprofessional communication and collaboration to pharmacists, preceptors and other healthcare professionals (El Hajj et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Reports of pharmacy students' and physicians' attitudes toward clinical pharmacy and interprofessional collaboration have been documented in various countries, but these concepts have yet to be explored in South Africa . In Qatar, pharmacy students reported having an overall positive attitude toward pharmaceutical care but also felt that providing pharmaceutical care takes too much time and effort .…”
Section: Introductionmentioning
confidence: 99%